Neurological Aspects of Overtraining Syndrome in Competitive Dance: A Narrative Review - Ignatowicz, Anna; Grylowska, Gabriela; Paluch, Anna; Gunia, Katarzyna; Adamczyk, Aleksandra; Banasik, Mateusz; Rebizant, Marcin; Palak, Andrzej; Żak, Agata; Tryba, Michał (Quality in Sport, 2026)
Background and aim: Overtraining Syndrome (OTS) is a maladaptive physiological and psychological response to prolonged high-intensity exercise without adequate recovery. Although musculoskeletal and endocrinological consequences of this condition are relatively well-documented, the neurological aspects of OTS remain underexplored. This narrative review aims to synthesize available evidence on the neurobiological mechanisms underlying OTS with special emphasis on the unique neurological demands of sport dance. Materials and methods: A narrative literature review was conducted using PubMed, Scopus, and Google Scholar databases. Search terms included: overtraining syndrome, competitive dance, sport dance, central fatigue, HPA axis, autonomic nervous system, serotonin, dopamine, neuroinflammation, cognitive function, and proprioception. Articles published between 2000 and 2025 in English were included. Studies pertaining to general athlete populations were included when dance-specific data were unavailable. Results: OTS in competitive dance involves dysfunction of the hypothalamic-pituitary-adrenal (HPA) axis, autonomic nervous system dysregulation, depletion of monoaminergic neurotransmitters (serotonin, dopamine), and neuroinflammatory processes. Dance-specific neurological vulnerabilities include impaired proprioception, disrupted motor engram execution, cerebellar and basal ganglia fatigue, and sleep-dependent motor memory consolidation deficits. Conclusions: The neurological profile of OTS in competitive dance is complex and multidimensional. The crucial aim is to early identificate the problem using validated psychometric tools, heart rate variability monitoring, and neurocognitive screening. A multidisciplinary approach — integrating sports medicine, neurology, and psychology — is essential for both prevention and treatment.